Three‐Dimensional Study of the Terminal Portion in Sprague‐Dawley Rat Ejaculatory Ducts. (13th August 2015) - Motohashi, M.; Inomata, T.; Takahashi, H.; Ichihara, N.; Kansaku, N.; Ikegami, M.; Asari, M.; Mutou, T.; Wakui, S.
Summary: In mammals, a pair of ejaculatory ducts exists in the urethra at the seminal colliculus. The detailed anatomical structures of the distal end of the ejaculatory ducts of Sprague‐Dawley rats were investigated by the computer‐assisted three‐dimensional reconstruction analysis using light‐microscopic serial sections. A three‐dimensional reconstruction revealed that in adult rats, the ejaculatory sinus pair consists of two parts: the cranial section – a compartment region composed of a fusion of the ampullary gland duct and the seminal vesicle duct, and the caudal section – a grooved region composed of a long slitlike ejaculatory ostium that extends into the urethra on both sides of the seminal colliculus. But the sphincter structure was not observed. The long axis of the compartment region was approximately 58  μ m in length, and that of the groove region was approximately 495  μ m. Although many epithelial glands ducts were distributed throughout the ejaculatory sinuses, the prostate and coagulation gland ducts did not open in these sinuses. The urethra was composed of transitional epithelium, while the ejaculatory sinuses were composed of single to stratified cuboidal epithelium. The ejaculatory ducts continued to the ejaculatory ostium in male adult Sprague‐Dawley rat were composed of the seminal vesicle ducts received the ampullary gland ducts.